2016
DOI: 10.17094/avbd.41280
|View full text |Cite
|
Sign up to set email alerts
|

The role of catecholamines in maintenance of homeostasis in digestive tract of domestic animals

Abstract: Absract Catecholamines have been identified after numerous studies at the turn of the nineteenth to the twentieth century. Their hormonal role is evident through their receptors and is very important on all of the organs and body systems. Except for the hormonal one, catecholamines also have the role of neurotransmitters. The role of catecholamines is evident in humans and domesticated animals in their digestive system. They strongly support, through their receptors, motility and secretion in stomach and small… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…It is a non-selective agonist and acts on the target cells through specific adrenergic receptors located on the CNS cell surface and in almost all peripheral tissues, and thus leads to blood vessel contraction in the body, increased cardiac muscle activity, relaxation of the smooth musculature of the stomach and bowels, dilation of pupils etc. (4,6,7).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is a non-selective agonist and acts on the target cells through specific adrenergic receptors located on the CNS cell surface and in almost all peripheral tissues, and thus leads to blood vessel contraction in the body, increased cardiac muscle activity, relaxation of the smooth musculature of the stomach and bowels, dilation of pupils etc. (4,6,7).…”
Section: Introductionmentioning
confidence: 99%
“…In small ruminants, specifically in sheep, the presence of adrenergic receptors in the smooth muscles of rumen was significantly higher than in comparison to cattle, where studies found receptors only in traces. Especially low levels of adrenergic receptor representation were found in the smooth muscles of dorsal and ventral bag of rumen (7,8).…”
Section: Introductionmentioning
confidence: 99%